The Influence of Social Media Marketing Activities on Brand Equity and Purchase Intention (Study of Silungkang Restaurant Instagram Followers) - Ilham Surya Vendri; Ratni Prima Lita; Verinita Verinita (Journal of Social Research, 2023)
This research aims to analyze the influence of social media marketing activities on brand equity and purchase intention (study on Instagram followers of Silungkang Restaurant). This explanatory research uses a survey. explanatory survey with a quantitative approach. Data collection on 250 Instagram followers of Silungkang Restaurant who were interested in buying food at Silungkang Restaurant was carried out using a purposive sampling technique. The data was then analyzed using Structural Equation Modeling - Partial Least Square (SEM-PLS). The research results show that social media marketing activities have a significant effect on brand equity. Brand equity has a significant effect on purchase intention, social media marketing activities have a significant effect on purchase intention, and social media marketing activities have a significant effect on purchase intention with brand equity as a mediating variable.